Apocynaceae sensun strictum from the Mucugê Municipal Park, Bahia, Brazil, including the valid publication of two names in Mandevilla Lindl. - Watanabe, Maurício Takashi Coutinho (2010)
The flora of Rauvolfioideae and Apocynoideae, which together form Apocynaceae s.s., from the Mucugê Municipal Park, Chapada Diamantina, State of Bahia, Brazil, is presented. Eight species and five genera were recognized. Mandevilla is the most diverse genus, with four species: M. scabra (Hoffmans. ex Roem. & Schult.) K. Schum., M. tenuifolia (J.C. Mikan) Woodson, M. bahiensis (Woodson) M.F. Sales & Kinoshita-Gouvêa, and M. microphylla (Stadelm.) M.F. Sales & Kinoshita-Gouvêa, the last two are a new status and a new combination, respectively, whose names are being validly published here. The four remaining genera are each represented by one species: Couma rigida Müll. Arg., Stipecoma peltigera (Stadelm.) Müll. Arg., Temnadenia violacea (Vell.) Miers, and Himatanthus bracteatus (A. DC.) Woodson. Identification key, descriptions, comments and illustrations are presented for every species.